2013
DOI: 10.1158/0008-5472.can-13-1755
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropilin-2 Is Upregulated in Lung Cancer Cells during TGF-β1–Induced Epithelial–Mesenchymal Transition

Abstract: The epithelial-mesenchymal transition (EMT) and its reversal, MET, are fundamental processes involved in tumor cell invasion and metastasis. SEMA3F is a secreted semaphorin and tumor suppressor downregulated by TGFβ1 and ZEB1-induced EMT. Here we report that NRP2, the high-affinity receptor for SEMA3F and a co-receptor for certain growth factors, is upregulated during TGFβ1-driven EMT in lung cancer cells. Mechanistically, NRP2 upregulation was TβRI-dependent and SMAD-independent, occurring mainly at a post-tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 59 publications
7
66
0
Order By: Relevance
“…Previously, we demonstrated that local tumor invasion in subcutaneous xenografts was NRP2-dependent (17). To extend these results to the isoforms, we subcutaneously injected H358 cells with endogenous NRP2 knockdown and reexpression of shRNA-resistant NRP2a and NRP2b into immunodeficient mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that local tumor invasion in subcutaneous xenografts was NRP2-dependent (17). To extend these results to the isoforms, we subcutaneously injected H358 cells with endogenous NRP2 knockdown and reexpression of shRNA-resistant NRP2a and NRP2b into immunodeficient mice.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that NRP2 was up-regulated during TGFβ-mediated EMT in NSCLC cell lines and that NRP2 knockdown inhibited TGFβ-mediated responses, including invasive tumor growth (17). Notably, nearly all reported NRP2 studies have involved the prototype NRP2a isoform, which is closely related throughout its entirety to NRP1.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 However, the potential involvement of VEGF-C in NRP2-mediated phenotypes in these studies was not discussed.…”
Section: Vegf-c and Neurophilinmentioning
confidence: 98%
“…51,52 Zinc finger E-boxebinding homeobox 1 and inhibitor of DNA-binding protein 2 have been shown to down-regulate SEMA3F in tumor cells, 30,53 but SEMA3F regulation in normal epithelial cells and its effects on ECs and vascular permeability are unclear.…”
Section: Discussionmentioning
confidence: 99%